Analisis Kebijakan Politik Hukum Pemerintah Kota Cilegon atas Peningkatan Pembangunan Ekonomi Tahun 2010-2015 - malik fatoni (Prodi Siyasah (Hukum Tata Negara) Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2018)
This article examines the effectiveness of making and stipulating regulations and legislation on efforts to increase economic development in Cilegon. Efforts to get achievements and progress for increasing economic development are necessary to conduct policy analysis on matters relating to political and legal policies and then to conduct a review of documents, observations and interviews. The legal political policy carried out by the Government of Cilegon can push for an increase in regional economic development. This can be seen from the legislative products validated by the Regional Legislative Assembly of Cilegon. Moreover, the quality and quantity are so good that the products can be carried out well by the executive and provide juridical power for the Government of Cilegon in increasing economic development as seen from the indicators of increasing economic development itself. Legal political policies that are processed and in synergy between government institutions in Cilegon indicate a strong and large commitment from these institutions to encourage and improve economic development in a sustainable and measurable manner.